Information Seeking Behavior of Santriwati of Madrasah Aliyah Pondok Pesantren Jakarta: A Study of Hofstede's Cultural Dimensions Perspective in Information Seeking Behavior - Liyanti, Lisda (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
The need of information is a basic need that is required to understand every moment in life. This is in accordance to the definition of information as an urge to overcome uncertainties or problems and to find solution and improvement. The need of information, be it a psychological, affective, or cognitive need, led someone to undertake an act of information seeking, known as information seeking behavior. The development of information seeking behavior nowadays expands into interdisciplinary study. One of them is using cultural dimension to have a better sight on the research. This paper discusses the information seeking behavior of the santri of the Madrasah Aliyah (Upper Secondary School students) Pondok Pesantren Jakarta, using the information seeking behavior Big Six Skill model from Eisenberg- Berkowitz, and two of Hofstede national cultural dimensions; Indonesian score of Power Distance and Individualism. This research will explore the uniqueness of Pondok Pesantren as one of typical Indonesian educational institution in coloring their students’ information seeking behavior.